System Thinking and Citizen Participation Is Still Missing in One Health Initiatives – Lessons From Fifteen Evaluations - Hitziger, Martin; Berezowski, John; Dürr, Salome; Falzon, Laura C.; Léchenne, Monique; Lushasi, Kennedy; Markosyan, Tigran; Mbilo, Céline; Momanyi, Kelvin N.; Özçelik, Ranya; Prejit, Nambiar; Zinsstag, Jakob; et al. (Frontiers in Public Health, 2021)
Tackling complex public health challenges requires integrated approaches to health, such as One Health (OH). A key element of these approaches is the integration of knowledge across sectors, disciplines and stakeholders. It is not yet clear which elements of knowledge integration need endorsement to achieve best outcomes. This paper assesses 15 OH initiatives in 16 African, Asian and European countries to identify opportunities to improve knowledge integration and to investigate geographic influences on knowledge integration capacities. Two related evaluation tools, both relying on semi-quantitative questionnaires, were applied to two sets of case studies. In one tool, the questions relate to operations and infrastructure, while the other assigns questions to the three phases of “design,” “implementation,” and “evaluation” of the project life cycle. In both, the question scores are aggregated using medians. For analysis, extreme values were identified to highlight strengths and weaknesses. Seven initiatives were assessed by a single evaluator external to the initiative, and the other eight initiatives were jointly assessed by several internal and external evaluators. The knowledge integration capacity was greatest during the project implementation stage, and lowest during the evaluation stage. The main weaknesses pointing towards concrete potential for improvement were identified to be a lack of consideration of systemic characteristics, missing engagement of external stakeholders and poor bridging of knowledge, amplified by the absence of opportunities to learn and evolve in a collective process. Most users were unfamiliar with the systems approach to evaluation and found the use of the tools challenging, but they appreciated the new perspective and saw benefits in the ensuing reflections. We conclude that systems thinking and associated practises for OH require not only specific education in OH core competencies, but also methodological and institutional measures to endorse broad participation. To facilitate meta-analyses and generic improvement of integrated approaches to health we suggest including knowledge integration processes as elements to report according to the COHERE guidelines.